The Buddhist Visnu : religious transformation, politics, and culture - Holt, John, 1948- (New York : Columbia University Press, 2004)
John Holt's groundbreaking study examines the assimilation, transformation, and subordination of the Hindu deity Visnu within the contexts of Sri Lankan history and Sinhala Buddhist religious culture. Holt argues that political agendas and social forces, as much as doctrinal concerns, have shaped the shifting patterns of the veneration of Visnu in Sri Lanka. Holt begins with a comparative look at the assimilation of the Buddha in Hinduism. He then explores the role and rationale of medieval Sinhala kings in assimilating Visnu into Sinhala Buddhism. Offering analyses of texts, many.
6 The Valiyak Mangalya: The Curative Powers of the Mala Raja7 Legacies of the "Buddhist Visnu": Myth and Cult at the Alutnuvara Devalaya; 8 Minister of Defense? The Politics of Deification in Contemporary Sri Lanka; Conclusion; Notes; Bibliography; Index of Place Names; Indext of Texts (Translated or Cited); Subject Index; Map.
Includes bibliographical references (pages 411-420) and indexes.
Print version record.
In English.
Master record variable field(s) change: 600, 650
Keywords: Vishnu -- (Hindu deity) -- Cult -- Sri Lanka; Buddhism -- Sri Lanka -- History; Buddhism -- Relations -- Hinduism; Hinduism -- Relations -- Buddhism; Buddhism and politics -- Sri Lanka; RELIGION -- Buddhism -- History; RELIGION -- Buddhism -- General; Buddhism; Buddhism and politics; Hinduism; Interfaith relations; Vishnu (Hindu deity) -- Cult; Sri Lanka; Andere Religionen; Buddhism and politics; Buddhism; Interfaith relations; Religion, Jewish Studies, Theology; Theology / Judaism / Religion; Electronic books; History; Electronic books